SHP2 inhibition improves celastrol-induced growth suppression of colorectal cancer - Zhang, Linxi; Hu, Xuefei; Meng, Qingying; Li, Ye; Shen, Hao; Fu, Yating; Zhang, Fan; Chen, Jiahui; Zhang, Wei; Chang, Wenjun; Pan, Yamin (Frontiers in Pharmacology, 2022)
This study aimed to explore novel targets for celastrol sensitization in colorectal cancer (CRC) based on differentially regulated signals in response to high- or low-dose celastrol. Targeting signals were investigated using western blot or phosphorylated receptor tyrosine kinase (RTK) arrays. Corresponding inhibitors for the signals were individually combined with low-dose celastrol for the assessment of combined anti-CRC effects, based on proliferation, apoptosis, colony assays, and xenograft models. The potential mechanism for the combination of celastrol and SHP2 inhibition were further examined. Low-dose celastrol (< 1 µM) did not effectively suppress AKT and ERK signals in CRC cells compared to high-dose celastrol (> 1 µM). However, when combined with an AKT or ERK inhibitor, low-dose celastrol could cooperatively suppress CRC proliferation. Furthermore, failed AKT or ERK inhibition by low-dose celastrol may be due to reactivated RTK-SHP2 signaling with negative feedback. The combination of celastrol and the SHP2 inhibitor resulted in greatly reduced AKT and ERK signals, as well as greater inhibition of CRC growth than celastrol alone. Moreover, the mechanism underlying combination suppression was also involved in activation of immune cell infiltration (mainly for CD8+ cells) in CRC tissues. Failure to inhibit RTK-SHP2-AKT/ERK signaling contributed to the lack of CRC growth suppression by low-dose celastrol. However, celastrol combination with the SHP2 inhibitor resulted in synergistic inhibition of CRC growth and provides a promising therapeutic target.